ANALYSIS OF THE BALANCE OF INTEREST PROTECTION OF DEBTORS AND CREDIBTORS IN THE BANKRUPTCY LAW - Fatihani Baso; Ayu Kholifah; Andi Novita Mudriani Djaoe; Redita Septia Sari. H (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2021)
The Bankruptcy Law is intended to maintain business continuity, not only debtors but also creditors and parties who are indirectly involved in the bankruptcy case. The purpose of the Bankruptcy Law is not to impoverish debtors and creditors and other parties but to ensure how after the bankruptcy decision the parties can resume their business or start a business again from scratch. The research approach used in this research is qualitative. The type of research is library research or normative juridical. Sources of data come from laws, journals, and books related to the Bankruptcy Law. The method of data collection is done through documentation in the form of books and journals. The data obtained were then processed and analyzed prescriptively and descriptively. Data processing is carried out by systematizing legal materials by classifying data to facilitate analysis and construction in normative legal research. The results of this study indicate that the Bankruptcy Law as far as possible maintains the balance of rights of debtors and creditors. Article 2 Paragraph (1) In simple terms, the procedure for bankruptcy of a person is also excluded if the debtor is hopelessly in debt or has no hope of continuing his business. Article 2 Paragraphs (2), (3), (4) and (5) provide limited access for certain lines to be bankrupt, seeing that these lines are in direct contact with the interests of the general public. Article 4 aims to maintain family harmony. Article 41 to maintain the continuity of the creditor's business when the debtor is in the process of bankruptcy.